Using In situ Dynamic Cultures to Rapidly Biofabricate Fabric-Reinforced Composites of Chitosan/Bacterial Nanocellulose for Antibacterial Wound Dressings - Zhang, Peng; Chen, Lin; Zhang, Qingsong; Hong, Feng F. (Frontiers in Microbiology, 2016)
Bacterial nano-cellulose (BNC) is considered to possess incredible potential in biomedical applications due to its innate unrivalled nano-fibrillar structure and versatile properties. However its use is largely restricted by inefficient production and by insufficient strength when it is in a highly swollen state. In this study, a fabric skeleton reinforced chitosan (CS)/BNC hydrogel with high mechanical reliability and antibacterial activity was fabricated by using an efficient dynamic culture that could reserve the nano-fibrillar structure. By adding CS in culture media to 0.25-0.75% (w/v) during bacterial cultivation, the CS/BNC composite hydrogel was biosynthesized in situ on a rotating drum composed of fabrics. With the proposed method, BNC biosynthesis became less sensitive to the adverse antibacterial effects of CS and the production time of the composite hydrogel with desirable thickness could be halved from 10 days to 5 days as compared to the conventional static cultures. Although its concentration was low in the medium, CS accounted for more than 38% of the CS/BNC dry weight. FE-SEM observation confirmed conservation of the nano-fibrillar networks and covering of CS on BNC. ATR-FTIR showed a decrease in the degree of intra-molecular hydrogen bonding and water absorption capacity was improved after compositing with CS. The fabric-reinforced CS/BNC composite exhibited bacteriostatic properties against Escherichia coli and Staphylococcus aureus and significantly improved mechanical properties as compared to the BNC sheets from static culture. In summary, the fabric-reinforced CS/BNC composite constitutes a desired candidate for advanced wound dressings. From another perspective, coating of BNC or CS/BNC could upgrade the conventional wound dressings made of cotton gauze to reduce pain during wound healing, especially for burn patients.